Quand des parents interprètent les normes scolaires : le cas du travail scolaire hors la classe en début de primaire - Françoise Robin (Recherches en Éducation)
On the basis of school tasks to which families are exposed and how they decipher such tasks, we try to identify what parents see of, and do with academic standards. By standards, we mean patterns which are binding and shared (Prairat, 2019), but also potentially transformative of the environment Canguilhem, 1996). Our study is in line with theories defending a "relational hypothesis" (Bautier and Goigoux, 2004) which considers that misunderstandings (Bautier & Rochex, 2007, Bautier & Rayou, 2013) play an important role in explaining educational inequalities. Parents' and children's reliance on misunderstandings can indeed result in remote interpretations of what the academic expectations are. We analyse parenting practices concerned with providing support in relation to homework. We interpret the support parents provide in terms of "renormalisation" (Schwartz, 2009): parents reinterpret the perceived academic standards and adjust them based on their share of responsibility for academic education (Glasman, 2004, 2013).